2012
DOI: 10.1242/jcs.108035
|View full text |Cite
|
Sign up to set email alerts
|

Nanopatterning Reveals an ECM Area Threshold for Focal Adhesion Assembly and Force Transmission that is regulated by Integrin Activation and Cytoskeleton Tension

Abstract: SummaryIntegrin-based focal adhesions (FA) transmit anchorage and traction forces between the cell and the extracellular matrix (ECM). To gain further insight into the physical parameters of the ECM that control FA assembly and force transduction in non-migrating cells, we used fibronectin (FN) nanopatterning within a cell adhesion-resistant background to establish the threshold area of ECM ligand required for stable FA assembly and force transduction. Integrin-FN clustering and adhesive force were strongly mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
132
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(142 citation statements)
references
References 82 publications
9
132
1
Order By: Relevance
“…Our observation that Y-27632 treatment accelerates cell movement with an accompanying loss of directionality is also in line with reports showing that RhoA/ROCK inhibition affects both the speed and directionality of cell movement by causing degradation of focal contacts and stress fibers [66][67][68]. The number and prominence of focal contacts have all been associated with an increase in the strength of cell-substratum adhesion [56,57,65,[69][70][71][72]. It thus came as a surprise that our MEFs that are devoid of focal contacts and stress fibers adhere more strongly to the substratum (Fig.…”
Section: Functional Consequences Of Irs-1 Inhibitionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our observation that Y-27632 treatment accelerates cell movement with an accompanying loss of directionality is also in line with reports showing that RhoA/ROCK inhibition affects both the speed and directionality of cell movement by causing degradation of focal contacts and stress fibers [66][67][68]. The number and prominence of focal contacts have all been associated with an increase in the strength of cell-substratum adhesion [56,57,65,[69][70][71][72]. It thus came as a surprise that our MEFs that are devoid of focal contacts and stress fibers adhere more strongly to the substratum (Fig.…”
Section: Functional Consequences Of Irs-1 Inhibitionsupporting
confidence: 90%
“…5 and 6, in which dark close contact areas cover nearly the entire undersurface. Close contacts associate with the cortical meshwork of actin microfilaments [57,83,83,84], so it is plausible that locally controlled contractility modulates cell surface geometry on a nanoscale, thus further contributing to cell adhesiveness [69,70,72,79,85]. It has also been observed that coated pits filled with ruthenium red-positive material seem to concentrate in areas of close contacts [86,87] possibly providing a wealth of charged molecules dangling from the cell surface.…”
Section: Functional Consequences Of Irs-1 Inhibitionmentioning
confidence: 99%
“…Alteration in cell morphology as a consequence of cytoskeletal tension has an indirect effect on mechano-transduction pathways, as demonstrated by expression changes in stem cell responses [14,29]. In the current studies cytoskeletal rearrangement were observed, including altered expression patterns of vinculin, a key structural component of focal adhesions [30]. On the LASER topography, vinculin displayed arrangement around the cell cytoplasm periphery.…”
Section: Discussionmentioning
confidence: 48%
“…In addition, we found that activated integrin β1 was significantly increased in SHR TA VSMCs vs. WKY VSMCs. Given the evidence that integrins are the principal mediators of mechanical signaling in cell–ECM interactions (Chen, Tan & Tien, 2004; Ciobanasu, Faivre & Le Clainche, 2013; Coyer et al., 2012; Schwartz & DeSimone, 2008), the increased expression and activity of integrin β1 in SHR VSMCs provide a potential mechanism for higher cell–ECM interactions in the 3D reconstituted model and may represent a potential target for the amelioration of aortic stiffening.…”
Section: Discussionmentioning
confidence: 99%